Oncostatin M Induces Heat Hypersensitivity by gp130-Dependent Sensitization of TRPV1 in Sensory Neurons. Issue 1 (23rd December 2011) - Langeslag, Michiel; Constantin, Cristina E; Andratsch, Manfred; Quarta, Serena; Mair, Norbert; Kress, Michaela
Oncostatin M (OSM) is a member of the interleukin-6 cytokine family and regulates eg. gene activation, cell survival, proliferation and differentiation. OSM binds to a receptor complex consisting of the ubiquitously expressed signal transducer gp130 and the ligand binding OSM receptor subunit, which is expressed on a specific subset of primary afferent neurons. In the present study, the effect of OSM on heat nociception was investigated in nociceptor-specific gp130 knock-out ( SNS-gp130 −/− ) and gp130 floxed ( gp130 fl/fl ) mice. Subcutaneous injection of pathophysiologically relevant concentrations of OSM into the hind-paw of C57BL6J wild type mice significantly reduced paw withdrawal latencies to heat stimulation. In contrast to gp130 f/fl mice, OSM did not induce heat hypersensitivity in vivo in SNS-gp130 −/− mice. OSM applied at the receptive fields of sensory neurons in in vitro skin-nerve preparations showed that OSM significantly increased the discharge rate during a standard ramp-shaped heat stimulus. The capsaicin- and heat-sensitive ion channel TRPV1, expressed on a subpopulation of nociceptive neurons, has been shown to play an important role in inflammation-induced heat hypersensitivity. Stimulation of cultured dorsal root ganglion neurons with OSM resulted in potentiation of capsaicin induced ionic currents. In line with these recordings, mice with a null mutation of the TRPV1 gene did not show any signs of OSM-induced heat hypersensitivity in vivo . The present data suggest that OSM induces thermal hypersensitivity by directly sensitizing nociceptors via OSMR-gp130 receptor mediated potentiation of TRPV1.